Study of database auditing tools accuracy. (2015) - Eljialy, A.E.M.
This study focuses on exploration of best ways to eliminate fraudulent activities in any organisation especially in financial institutions, as detecting fraud earlier will prevent the chances of loss of revenue. Different crime detecting techniques have been tested in this research work. However, the previous investigating techniques appear to be with loopholes. Our security methodology is based on three tools (logminer, audit_trail and flashback). Indeed, the database suspicious activities can only be detected by implementing database auditing technique. It has been proven in this study that database auditing tool is effective tool in detecting any fraudulent activities in database system. Thus, this technique is highly recommended to be applied in various institutions dealing with databases. The experimental findings of this research have proven quite efficient forensic time stamp precision between the above mentioned tools; however, the logminer tool appears to be most accurate one.